Optimizing Supervision Innovation: A Case Study of the Inspectorate in Sungai Penuh City - Herlina, Vivi; Sestriyenti, Enny (Universitas Negeri Surabaya, 2023)
Technology requires all government agencies to utilize the results of innovation in carrying out their activities. This study aims to determine the utilization of technology in surveillance activity at Inspektorat Kota Sungai Penuh and identify supporting and obstacle factors in applying innovation. This study used a qualitative approach and a guided interview technique to collect data. Criterion sampling was used to specify the respondents. The respondents were the Inspector, Head of Sub-division General Administrative and Financial, Head of Sub-division Analysis and Evaluation, Middle Auditor, and Junior Auditor. This study showed that utilizing innovation at the Inspektorat Kota Sungai Penuh is a process, service, and method innovation. The Inspektorat of Kota Sungai Penuh is utilizing technology products in surveillance by using SIM HP, SIPTL, SiBijak, and Consulting Clinics. The supporting factors in optimizing technology are leadership encouragement, facility availability, and adequate human resources. Conversely, the inhibiting factor consists of a limited budget and employee mutations.